An Overview of Child Resistant Pharmaceuticals Packaging - Stanekzai, Azimullah (Journal of Natural Sciences – Kabul University, 2022)
Before a medicinal product for human use is placed on the market, it generally undergoes extensive studies, including preclinical tests and clinical trials, to ensure its safety, high quality, and effectiveness for the target population. According to the World Health Organization (WHO), the third-leading cause of unintentional death in children under age 14 is acute poisoning. WHO estimates that 3,000 children in this age group die each year, with 90% of those poisonings occurring at home. In addition, drugs are the leading cause of non-fatal poisoning in children in middle-income and high-income countries. Child-resistant (CR) packaging is used to minimize the risk of children accessing or ingesting medication and is one of the best-documented successes in preventing unintentional poisoning in children.